Asksia AI LOGO

Sia

Question
Math
Posted 11 months ago
check answer
\therefore Find pp from p=ρF\boldsymbol{\nabla} p=\rho \mathbf{F} in the case where
F=(axby,ay+bx,a) and ρ=(x2+y2)z,
\mathbf{F}=(a x-b y, a y+b x, a) \text { and } \rho=\left(x^{2}+y^{2}\right)^{-z},

with constants a,ba, b.
Sign in to unlock the answer
Answer from Sia
Posted 11 months ago
Solution by Steps
step 1
To find p p from p=ρF \boldsymbol{\nabla} p = \rho \mathbf{F} , we need to solve the equation given the vector field F \mathbf{F} and the scalar field ρ \rho
step 2
Given F=(axby,ay+bx,a) \mathbf{F} = (ax - by, ay + bx, a) and ρ=(x2+y2)z \rho = (x^2 + y^2)^{-z} , we can equate p \boldsymbol{\nabla} p to ρF \rho \mathbf{F}
step 3
Solving the equation π200p=(x2+y2)z(axby,ay+bx,a) \frac{\pi}{200} p = (x^2 + y^2)^{-z} (ax - by, ay + bx, a) for p p , we get different cases for the solution
step 4
For the case where b=a b = -a and x=0 x = 0 and y=1 y = 1 , we find p=200aπ p = \frac{200a}{\pi}
step 5
For the case where x0 x \neq 0 and (x2+14(14x2+4x+1)2)z0 (x^2 + \frac{1}{4}(1 - \sqrt{-4x^2 + 4x + 1})^2)^z \neq 0 , we find p=200a(x2+14(14x2+4x+1)2)zπ p = \frac{200a(x^2 + \frac{1}{4}(1 - \sqrt{-4x^2 + 4x + 1})^2)^{-z}}{\pi} and b=a(4x2+4x+1+1)2x b = \frac{a(\sqrt{-4x^2 + 4x + 1} + 1)}{2x} and y=12(14x2+4x+1) y = \frac{1}{2}(1 - \sqrt{-4x^2 + 4x + 1})
step 6
For the case where x0 x \neq 0 and (x2+14(4x2+4x+1+1)2)z0 (x^2 + \frac{1}{4}(\sqrt{-4x^2 + 4x + 1} + 1)^2)^z \neq 0 , we find p=200a(x2+14(4x2+4x+1+1)2)zπ p = \frac{200a(x^2 + \frac{1}{4}(\sqrt{-4x^2 + 4x + 1} + 1)^2)^{-z}}{\pi} and b=a(4x2+4x+11)2x b = -\frac{a(\sqrt{-4x^2 + 4x + 1} - 1)}{2x} and y=12(4x2+4x+1+1) y = \frac{1}{2}(\sqrt{-4x^2 + 4x + 1} + 1)
step 7
For the case where p=0 p = 0 and (y1)y(y2)z0 (y - 1)y(y^2)^z \neq 0 , we find a=0 a = 0 and b=0 b = 0 and x=0 x = 0
Answer
The value of p p depends on the specific case and values of a a , b b , x x , y y , and z z . The solutions are given by the cases in steps 4 to 7.
Key Concept
Gradient and Scalar Field Multiplication
Explanation
The key concept involves solving for a scalar field p p when its gradient is given by the product of another scalar field ρ \rho and a vector field F \mathbf{F} . The solution requires equating the gradient of p p to this product and solving for p p under different conditions for the variables involved.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question